Aquisição de bens e serviços públicos via pregão eletrônico: um estudo sobre o preço final - Souza, Luís José de Menezes e (2008)
Seeking to raise up efficiency in government procurement procedures it has been implemented an innovation in the law which constitutes for correct basis justifying on the procedures of purchase. For innovation itself it is employed electronic floor use or reverse auction, compulsory since 10,520 law publication that regulates these procurement. At this purpose, every round negotiation, proponents reduce their prices and they seek to effect recruitment, spite of other competitors. This paper presents an economic kind that allows profiting with some competitors alone to do a better assessment of its commercial organization especially during sale on electronic floor. Model was developed aiming at submitted the application in Brazilian government market purchases without specifying aspects from a specific segment to industry. Econometrics model proposed for general application implemented through government purchases through electronic stock.